Detection of serum hepatitis B virus DNA in patients with chronic hepatitis using the polymerase chain reaction assay. - Kaneko, S (1989)
We compared the sensitivity of the polymerase chain-reaction (PCR) assay to that of slot-blot hybridization for detecting hepatitis B virus (HBV) DNA in the serum of 31 patients with chronic hepatitis. Of 14 chronic hepatitis patients positive for both HBV surface and HBV e antigens, 9 were positive for HBV DNA by slot-blot hybridization and all 14 by PCR. Also, of 9 patients positive for HBV surface antigen and antibody against HBV e antigen, 2 were positive for HBV DNA by slot-blot analysis and 8 by PCR. Finally, in 8 patients positive for HBV DNA by slot-blot hybridization, but 4 were positive by PCR. We find that analysis by the PCR technique provides a greater than 10(4)-fold increase in sensitivity over the slot-blot hybridization assay. This result represents an important breakthrough in sensitivity because it is now possible to detect as few as three HBV DNA genomes per sample of serum.